2015
DOI: 10.1098/rsif.2015.0652
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow through the embryonic heart outflow tract during cardiac looping in HH13–HH18 chicken embryos

Abstract: Blood flow is inherently linked to embryonic cardiac development, as haemodynamic forces exerted by flow stimulate mechanotransduction mechanisms that modulate cardiac growth and remodelling. This study evaluated blood flow in the embryonic heart outflow tract (OFT) during normal development at each stage between HH13 and HH18 in chicken embryos, in order to characterize changes in haemodynamic conditions during critical cardiac looping transformations. Two-dimensional optical coherence tomography was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 57 publications
(111 reference statements)
7
46
0
Order By: Relevance
“…The results of peak blood flow velocity in the embryonic heart are comparable with the range of hemodynamic measurements in the mouse embryos from other developmental stages measured in utero using Doppler ultrasonic imaging . Also, our measured velocity values are comparable to those from the chick embryonic heart obtained with OCT . These data suggest the feasibility of our approach to perform quantitative 2D spatially‐resolved measurements of the absolute blood flow velocity inside the mouse embryonic heart.…”
Section: Resultssupporting
confidence: 82%
“…The results of peak blood flow velocity in the embryonic heart are comparable with the range of hemodynamic measurements in the mouse embryos from other developmental stages measured in utero using Doppler ultrasonic imaging . Also, our measured velocity values are comparable to those from the chick embryonic heart obtained with OCT . These data suggest the feasibility of our approach to perform quantitative 2D spatially‐resolved measurements of the absolute blood flow velocity inside the mouse embryonic heart.…”
Section: Resultssupporting
confidence: 82%
“…With the advent of new imaging modalities, as well as the use of models that allow in-vivo assessment of mechanical forces, is it possible to link the two. These techniques range from in-vivo confocal microscopy [32,42], micro-computed tomography [43], high-frequency ultrasound, and optical coherence tomography [44,45]. Detailed analysis of cardiac flow has revealed that despite the existence of unidirectional flow through the developing blood vessels, flow in the embryonic heart is bidirectional, which exposes the heart to unique spatial shear stress [46].…”
Section: Mechanical Forces In Heart Developmentmentioning
confidence: 99%
“…Embryology is a major research area where OCT shows great promise as a high-resolution unlabeled imaging tool [31][32][33]. With the primary focus on the cardiovascular development and abnormalities, OCT has been reported able to reveal detailed structures of the embryonic heart comparable to histology [34][35][36], to capture four-dimensional dynamic cardiac activities [37][38][39], to quantify biomechanics of the heart tube [40][41][42], to assess cardiac hemodynamics [43][44][45], to characterize novel mutant heart phenotypes [46][47][48], and to investigate cardiac responses to physical and chemical manipulations [49][50][51][52]. Focusing on the mouse model, our group has combined OCT with live embryo culture to establish a number of structural and functional imaging methods [39,45,48,[53][54][55], suggesting an important role of OCT for in vivo analysis of the mammalian embryo.…”
Section: Introductionmentioning
confidence: 99%